Assessment of Health Financing Options : Papua New Guinea - World Bank (Washington, DC, 2015)
Papua New Guinea s (PNG) health system is characterized by low health inputs per capita, low health service contact rates and significant inequities in health care use. Health spending relative to GNI per capital and as a revenue share of GDP is low. Government spending as a share of total health expenditure is, however, high and the financing system is dependent on a number of complex interactions between a number of agencies, both at the national and subnational level. Anecdotal evidence suggests that out-of-pocket (OOP) spending is minimal. The current system of health financing has not delivered improved health outcomes; in fact health outcomes in PNG have been stagnant in recent decades. PNG is not on track to meet any of the health-related Millennium Development Goals (MDGs). Significant investment in the heath sector is needed to address the decline, meet current demographic trends and address inefficiencies and inequities. These additional resource requirements will have to be met while maintaining the high levels of financial risk protection and relatively equitable access to health care. The additional resource requirements will have to be financed in a sustainable manner. This report examines three broad health financing options in PNG: (i) increasing the level of general revenue spending; (ii) introducing contributory, insurance-based health financing arrangements; and (iii) mobilizing additional resources through efficiency savings in the sector. The three options are not mutually exclusive.